On the Capacity of V2X Communication Networks to Support the Delivery of Emerging C-ITS Services: A Case Study on an Irish Motorway - Arif Hossan; Md Noor-a-Rahim; Cormac J. Sreenan; Piraba Navaratnam; Shobanraj Navaratnarajah; Thomas Allen; David Laoide-Kemp; Aisling O’Driscoll (Information, 2025)
Roadside communication networks with Cooperative Intelligent Transport Systems (C-ITSs) offer services that aim to enhance traffic management and road safety.This paper presents a comprehensive scalability study of C-ITSs to support a deployment of Day 1 advisory services on the busiest Irish motorway. Specifically, the performance of the two standardized C-ITS short-range communication technologies, namely ITS-G5 and C-V2X, are quantified. Both technologies are evaluated while considering different market penetration rates (MPRs), real-world vehicle densities during daily time periods, and data traffic demands linked to real world C-ITS services. The simulation results show that ITS-G5 performs slightly better at shorter distances, and C-V2X performs marginally better at medium and longer distances, benefiting from technology that supports better signal quality and communication robustness.